Pentingnya Membangun Platform Kolaborasi Multi-Stakeholder sebagai Key Enabling Factor dalam Membangun Ekosistem Inovasi Industri 4.0 di Era New Normal - Utomo, Satrio; Harjono, Agus Nugroho (Jurnal Informatika Universitas Pamulang, 2021)
Industry 4.0 is an era of technological disruption or industrial revolution 4.0 because it puts more emphasis on system automation and connectivity which will make the mobility of the industrial world movement andÂ  job competition non-linear . The use of digital technology is one of the keys. Industry opportunities for industrial development 4.0 are an effort to increase industrial competitiveness, but many industries do not yet understand the concept and how to start the stages. One of the ways proposed as a policy in preparing industry 4.0 should be taken a multi-stakeholder collaborative approach to facilitate development, including gathering digital transformation initiatives so that limited resources can be optimal. As a form of soft industry policy, a platform organization is also needed as a sustainable program manager and provides technical facilities. From a technical point of view, it is necessary to prepare enabling technology that can be utilized by all actors in the cross-sectoral digital economy in an affordable manner. The Ecosystem Platform becomes a medium to be able to build synergy and collaborative across industries with all stakeholders in an effort to accelerate the transformation of industry 4.0 according to the national priority program of Making Indonesia 4.0. In line with that, coordination was carried out between parties in the industrial transformation 4.0 process, as well as building networks to develop positive cooperation, including government, academics or R&D, industry players / associations, technical providers, consultants and of course financial actors in accelerating the industrial transformation process 4.0.